Peningkatan Kemampuan Menulis Puisi Melalui Model Think Talk Write pada Siswa Kelas VIII SMP Swasta Kristen Tomosa 1 - Gulo, Testing Ilmiah; Bawamenewi, Arozatulo; Zega, Imansudi; Waruwu, Lestari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The aim of this research is to enhance the ability to write free verse poetry through the application of the think talk write learning model for eighth-grade students at Tomosa 1 Christian Private Junior High School. The type of research is Classroom Action Research (CAR) with a procedure that consists of planning, action, observation, and reflection. The research instruments include poetry text sheets, teacher observation sheets, researcher observation sheets, and field notes. The subjects of the research are 30 eighth-grade students. The research was conducted over two cycles. The results showed that in the first cycle, the percentage of classical completeness was 10%, while in the second cycle, the percentage of classical completeness rose to 90%. Observations were conducted on researchers and students which showed the results of the researchers' activity percentage in cycle I, the first meeting was 61.11%, while the second meeting was 77.78%, and in cycle II, the first meeting was 89.99%, while the second meeting was 94.44%. Furthermore, the percentage of students' activities in cycle I, the first meeting was 50.6%, while the second meeting was 77.6%, and the percentage in cycle II for the first meeting was 91%, while the second meeting was 96.6%. Thus, it is concluded that the implementation of the think talk write learning model can improve the ability to write poetry.